2021
DOI: 10.1139/cjm-2020-0290
|View full text |Cite
|
Sign up to set email alerts
|

Evolving the core microbial community in pit mud based on bioturbation of fortified Daqu

Abstract: Directional stress is an effective measure to evolve community structure and improve bioactivity of pit mud (PM). In this study, adding fortified Daqu in artificial PM (APM) was to disturb the microbial community and affect the metabolites furthermore. To evaluate the effect of fortified Daqu on culturing APM, microbial communities of APMs with/without adding fortified Daqu were investigated by fluorescence in situ hybridization and Illumina Miseq. These results indicated that microbes (Clostridium sp., Clostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Chen et al . also found that the abundance of Lactobacillus was increased at the later fermentation stage after inoculating bio‐augmented Daqu 29 . There was also no obvious change in the fungal community after day 6 of fermentation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Chen et al . also found that the abundance of Lactobacillus was increased at the later fermentation stage after inoculating bio‐augmented Daqu 29 . There was also no obvious change in the fungal community after day 6 of fermentation.…”
Section: Discussionmentioning
confidence: 80%
“…28 Chen et al also found that the abundance of Lactobacillus was increased at the later fermentation stage after inoculating bio-augmented Daqu. 29 There was also no obvious change in the fungal community after day 6 of fermentation. This result was also obtained by Cui et al 30 Temperature is a key factor in the structure of microbial communities during fermentation.…”
Section: Correlation Analysis Of Microbial Community and Aroma Compou...mentioning
confidence: 94%
“…Daqu not only provides the microbial consortium, enzymes (e.g., α-amylase and glucoamylase), and partial raw materials for alcoholic fermentation, but also significantly contributes aroma compounds [2,3,[8][9][10][11][12]. Previous studies of Daqu mainly focused on its microbial community profile and enzyme composition [3,4,8,9,[13][14][15][16][17][18], the dynamics of microbial succession in the Daqu manufacturing process [19][20][21][22], the effects of fortified Daqu on the microbial composition and flavor ingredients of Baijiu [23][24][25][26][27], and how environmental factors (e.g., moisture, acidity, and temperature) affect the microbial structure and enzymatic activity of Daqu [6,15,28].…”
Section: Introductionmentioning
confidence: 99%